The Effect of Plant Growth Promoting Fungi Mycorrhiza and Trichoderma on The Productivity of Edamame Soybean Plants (Glycine Max (L.) Merrill) - Nurfadila; Trisnani Alif; Nur Aisyah, Mahindra Dewi; Erdiansyah, Iqbal (University of Jember, 2025)
Sustainable edamame cultivation using Plant Growth Promoting Fungi (PGPF) Mycorrhiza sp and Trichoderma sp is still not widely applied by Indonesian farmers. The purpose of this research was to test the effect of plant growth promoting fungi Mycorrhiza sp and Trichoderma sp on the productivity of edamame soybean plants. This research was conducted from June to September 2024 at Jember City. The research design used was a Completely Randomized Design (CRD) with 4 levels with 5 replications until there were 20 experimental units with treatment levels, P0: 0 gr/plant (Negative control), P1: 15 gr/plant Mycorrhiza sp, P2: 15 gr/ plant Trichoderma sp, P3: 15 gr/plant both PGPF (7.5 gr/ plant Mycorrhiza sp + 7.5 gr/ plant Trichoderma sp). Observation variables include plant height, trifoliate, productive branches, flowering age, root infection. The research results show that the observation variables of plant height and productive branches have different results that are not significant while trifoliate had an effect of treatment on the observation of variables of week 1 and week 2 and the observation variables of flowering age it shows that the first flowers appeared at the age of 42 dap and root infection had an effect which is indicated by the presence of hyphae on the roots of soybean plants. The Treatment of PGPF Mycorrhiza sp and Trichoderma sp had an effect on the observation of flowering age and root infection, while the single treatment Mycorrhiza sp had an effect on the observation of the number of trifoliate leaves.